Development of a nano‐gold immunodiagnostic assay for rapid on‐site detection of invasive aspergillosis. Issue 9 (September 2019) - Raval, Komal M.; Ghormade, Vandana; Rajamohanan, P. R.; Choudhary, Hansraj; Rudramurthy, Shivaprakash M.; Chakrabarti, Arunaloke; Paknikar, Kishore
N/A: Introduction. : Timely detection of invasive aspergillosis (IA) caused by fungal pathogens, i.e. Aspergillus fumigatus and Aspergillus flavus, in immunocompromised patients is crucial in preventing high mortality. Aim. : To develop a simple immunoassay for the detection of galactomannan (GM), an IA biomarker. Methodology. : GM from A. fumigatus and A. flavus clinical strains was purified and characterized by X‐ray diffraction, IR spectroscopy and 13 C/ 1 H nuclear magnetic resonance (NMR) for polyclonal antibody (pAb) production in rabbits. An enzyme‐linked immunosorbent assay (ELISA) was standardized using concanavalin A to capture Aspergillus GM and pAbs to detect it. Gold nanoparticles (AuNPs) were synthesized and conjugated to pAbs for the development of a dot‐blot immunoassay. The developed dot‐blot was evaluated with 109 clinical serum and bronchoalveolar lavage samples. Results. : Spectroscopy studies characterized the d‐galactofuranosyl groups of GM responsible for the immune response and generation of pAbs. The ELISA employing pAbs showed a sensitivity of 1 ng ml −1 for Aspergillus GM. Furthermore, a sensitive, visual, rapid dot‐blot assay developed by the conjugation of pAbs to AuNPs (˜24±5 nm size, −36±2 mV zeta potential) had a detection limit of 1 pg ml −1 in serum. The pAbs interacted with Aspergillus spp. but did not cross‐react with other fungal pathogen genera such as Penicillium and Candida. Evaluation of the dot‐blot with 109 clinical samples showed high sensitivity (80%) and specificity (93.2%), with an overall assay accuracy of 89%. Conclusion. : The developed nano‐gold immunodiagnostic assay has immense potential for practical use in rapid, specific and sensitive on‐site diagnosis of IA, even under resource‐limited settings.